Knowledge, Habits and Attitudes in Photoprotection to Prevent Skin Cancer - Asbely Yera Sánchez; Yanet Blanco Fleites; Yuleydi Alcaide Guardado; Mario Ávila Sánchez; Greta Margarita Arrechea García; Jacobo Cambil Martín (Revista Finlay)
Foundation: skin cancer is one of the most common neoplasms, with an increase in the last two decades. Photoprotection campaigns have had a positive impact on the population and allow healthy people to care for their skin and prevent cancer. Objective: to describe the main results obtained in scientific studies related to knowledge, habits and attitudes in photoprotection for the prevention of skin cancer in a population at risk over 18 years of age. Method: a systematic review was carried out in the databases Scopus and Pubmed in (English), Scielo and CUIDEN in (Spanish), with access profile from the electronic library of the University of Granada in the study period from May 2018 to July 2022. The guiding question was developed through the PICOT acronym, search terms and the descriptors in Health Sciences and Medical Subject Headings were used, respectively. Results: knowing risk and protective behaviors is useful to guide individual or community-level interventions to reduce morbidity associated with sun exposure. Skin cancer prevention campaigns have been shown to be effective and cost-effective. Primary care physicians play an important role in skin cancer prevention. Counseling on modifiable risk factors and strategies to avoid the sun, in patients with a personal or family history of skin cancer, should be part of preventive medicine. Conclusions: scientific studies that address knowledge, habits and attitudes in relation to photoprotection for the prevention of skin cancer, highlight among their main results that the main conduct to guarantee adequate healthy protective action is to direct education programs in primary prevention of health.